Direct visualization by FRET-FLIM of a putative mechanosome complex involving Src, Pyk2 and MBD2 in living MLO-Y4 cells - Day, Richard N.; Day, Kathleen H.; Pavalko, Fredrick M. (PloS one, 2021)
Earlier, we proposed the “mechanosome” concept as a testable model for understanding how mechanical stimuli detected by cell surface adhesion molecules are transmitted to modulate gene expression inside cells. Here, for the first time we document a putative mechanosome involving Src, Pyk2 and MBD2 in MLO-Y4 osteocytes with high spatial resolution using FRET-FLIM. Src-Pyk2 complexes were concentrated at the periphery of focal adhesions and the peri-nuclear region. Pyk2-MBD2 complexes were located primarily in the nucleus and peri-nuclear region. Lifetime measurements indicated that Src and MBD2 did not interact directly. Finally, mechanical stimulation by fluid flow induced apparent accumulation of Src-Pyk2 protein complexes in the peri-nuclear/nuclear region, consistent with the proposed behavior of a mechanosome in response to a mechanical stimulus.